Effects of sevoflurane and adenosine receptor antagonist on the sugammadex‐induced recovery from rocuronium‐induced neuromuscular blockade in rodent phrenic nerve-hemidiaphragm tissue specimens - Yong Beom Kim; Jae‐Moon Choi; Chungon Park; Hey‐Ran Choi; Junyong In; Hong‐Seuk Yang (Wiley, 2021)
Abstract Sevoflurane affects on the A1 receptor in the central nervous system and potentiates the action of neuromuscular blocking agents. In the present study, we investigated whether sevoflurane (SEVO) has the ability to potentiate the neuromuscular blocking effect of rocuronium and if the specific antagonist of adenosine receptor (SLV320) can reverse this effect. In this study, phrenic nerve-hemidiaphragm tissue specimens were obtained from 40 Sprague-Dawley (SD) rats. The specimens were immersed in an organ bath filled with Krebs buffer and stimulated by a train‐of‐four (TOF) pattern using indirect supramaximal stimulation at 20 s intervals. The specimens were randomly allocated to control, 2‐chloroadenosine (CADO), SEVO, or SLV320 + SEVO groups. In the CADO and SLV320 + SEVO groups, CADO and SLV320 were added to the organ bath from the start to a concentration of 10 μM and 10 nM, respectively. We then proceeded with rocuronium‐induced blockade of >95% depression of the first twitch tension of TOF (T1) and TOF ratio (TOFR). In the SEVO and SLV320 + SEVO groups, SEVO was added to the Krebs buffer solution to concentration of 400-500 μM for 10 min. Sugammadex‐induced T1 and TOFR recovery was monitored for 30 min until >95% of T1 and >0.9 of TOFR were confirmed, and the recovery pattern was compared by plotting these data. T1 recovery in the SEVO and CADO groups was significantly delayed compared with the control and SLV320 + SEVO groups (p < .05). In conclusion, sevoflurane affects on the A1 receptor at the neuromuscular junction and delays sugammadex‐induced recovery from neuromuscular blockade.